Classroom talk : evidence-based teaching for enquiring teachers - Knight, Rupert (Critical Publishing, 2020)
Written for teachers, this concise guide takes an evidence-based approach to oracy / classroom talk with practical advice on how to engage with and evaluate the ideas explored.